Gender and authorship of publications from Pediatric Acute Lung Injury and Sepsis Investigators (PALISI) - Jeyapalan, Asumthia S.; Brown, Stephanie R.; Gaspers, Mary G.; Haliani, Brittany; Kudchadkar, Sapna R.; Rowan, Courtney M.; Gertz, Shira J. (Frontiers in Pediatrics, 2023)
Introduction Pediatric Acute Lung Injury and Sepsis Investigators (PALISI) is a network fostering clinical research to optimize care for critically ill children. We aim to examine the efforts of the PALISI Network to increase gender parity in research, as evidenced by authorship. Methods The first and senior authors of all published PALISI articles from 2002 to 2021 were analyzed for gender of presentation. Funding sources, impact factors, professional roles, and location were extracted. Results We identified 303 articles, 61 published from 2002 to 2011, and 242 from 2012 to 2021. There were 302 first authors, representing 188 unique individuals, and 283 senior authors, representing 119 unique individuals. Over half (55.6%, n = 168) of the first authors were women. More women were first authors from 2012 to 2021 (n = 145, 60.2%) as compared to the years 2002–2011 [37.7%, n = 23, OR = 2.50 (95% CI: 1.40, 4.45, p = 0.002)]. Senior authors were 36.0% (n = 102) women, with no change over time. Women senior authors had a higher proportion of women first authors (67.7% vs. 32.4%, p = 0.017). No gender differences were noted based on article type or impact factor. The majority of authors came from institutions in the United States. Women had comparatively more NIH and CDC funding but received less funding from foundations and AHRQ. Discussion In PALISI publications, first authorship by women has increased over time, such that it now exceeds both the proportion of women pediatric intensivists and women first authors in critical care publications. Senior authorship by women has been stagnant. A multifactorial approach by individuals, institutions, networks, and journals is needed to bring senior women authors to parity.